Repetitive head impact exposure and later‐life plasma total tau in former National Football League players. Issue 1 (9th December 2016) - Alosco, Michael L.; Tripodis, Yorghos; Jarnagin, Johnny; Baugh, Christine M.; Martin, Brett; Chaisson, Christine E.; Estochen, Nate; Song, Linan; Cantu, Robert C.; Jeromin, Andreas; Stern, Robert A.
Abstract: Introduction: Blood protein analysis of total tau (t‐tau) may be a practical screening biomarker for chronic traumatic encephalopathy (CTE), a neurodegenerative tauopathy associated with repetitive head impact (RHI) exposure. We examined plasma t‐tau in symptomatic former National Football League (NFL) players compared with controls and the relationship between RHI exposure and later‐life plasma t‐tau. Methods: Ninety‐six former NFL players (age 40–69) and 25 same‐age controls underwent blood draw to determine plasma t‐tau levels. The cumulative head impact index (CHII) quantified RHI exposure. Subjects completed measures of clinical function. Results: A higher CHII predicted greater plasma t‐tau in the former NFL players ( P  = .0137). No group differences in plasma t‐tau emerged, but a concentration ≥3.56 pg/mL was 100% specific to former NFL players. Plasma t‐tau did not predict clinical function. Discussion: Greater RHI exposure predicted higher later‐life plasma t‐tau concentrations, and further study on plasma t‐tau as a candidate screening biomarker for CTE is warranted.